UPAYA PENINGKATAN PRODUKTIVITAS DAN KESEJAHTERAAN PETERNAK DI DESA TEGALREJO KABUPATEN BLITAR - Hadi Rahmad; Zulfa khalida; Eti Putranti (Jurnal Pengabdian kepada Masyarakat, 2025)
Most breeders used fresh green feed for theirs sheep or goat. They had not added concentrate feed because they did not know the exact dosage for processing concentrate and the feed machine's capabilities were limited. The Team has made a mixing machine and bought a grinding machine to be given for the breeders' association in Desa Tegalrejo. The Team has also trained breeders to make concentrate. The results of evaluation show that 100% of breeders strongly agree that PPM activities gave the effect of increasing competitiveness